Kajian Penawaran Tenaga Kerja Dan Potensi Yang Dimiliki Rumahtangga Serta Kesempatan Kerja Pada Sektor Non-Pertanian Dan Pertanian Di Kabupaten Toba Samosir - Ahmad Husin Lubis (Islamic Education Journal, 2022)
The findings of the study in Toba Samosir Regency showed that in women rice farmers the influence of each independent variable individually which significantly affected the dependent variable was as follows. The wife's education, husband's education, the length of time her husband has been abroad and the Toba Batak Tradition regarding the dominance of women farmers in rice farming have a real effect. The results of the regression analysis show that the higher the education of the wife, the less time the wife spends on rice farming. This is because the higher the education level of the wife, the more varied the work she can do, such as opening a grocery store or trading ulos. The results of the regression analysis show that the higher the husband's education, the less time his wife spends on rice farming. This is because the higher the husband's education level, the wider his thinking perspective will lead to higher gender tolerance. Therefore, the husband's desire to ease his wife's work in the fields will be greater so that it can reduce the outpouring of the wife's working time (female farmers) in rice farming. The longer the period of time that the husband (male farmer) has traveled to the capital city of North Sumatra and DKI Jakarta, the less time his wife (female farmer) has worked in rice farming. This is because in overseas, husbands can see and compare the pattern of life in Toba Samosir with other areas so that awareness of gender equality begins to form and begins to devote part of his time to helping his wife in rice farming activities.